Marx's Financial Capitalism. Issue 1 (3rd April 2019) - Nishibe, Makoto
Abstract: This study shows that "financialization, " widely accepted as a theoretical framework representing the structural change in modern capitalist economy, is one aspect of the "free investment capitalism" that resulted from globalization and deindustrialization as the long-term institutional and technological trends since the 1970s. Globalization is understood as the tendency for the simultaneous expansion (more accurately, extensive expansion and intensive deepening) of market and the reduction of state and community. Its ultimate goal is free investment capitalism, in which fictitious capital is ubiquitous and free investment in it is totally pursued. The study theoretically sees it as G mode (general mode) capitalist market economy with general commodification of labor power as seen in human capital investment and financialization of labor power.